Metal Complexes of π-Expanded Ligands (3): Synthesis and Characterization of tris[2-[(octylimino)methyl]-1-pyrenolato-N,O] cobalt(III) - Xuan Dien, Luong; Kim Nga, Nguyen; Thi Tuyet Mai, Nguyen; Xuan Truong, Nguyen; Yamashita, Ken-ichi; Sugiura, Ken-ichi Sugiura (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 2DO - 10.25073/2588-1140/vnunst.4898, 2019)
Abstract: The reactions of Co(OAc) 2 with two equivalents of 1-hydroxy-2-[(octylimino)methyl-pyrene L , performed in air, lead to the formation of the cobalt(III) complex, tris[2-[(octylimino)methyl]-1-pyrenolato-N,O] cobalt(III) CoL 3 , accommodating three chelating pyrene-based salicylaldiminato-type ligands. The complex CoL 3 and the referent tris(salicylaldiminato) cobalt(III) 1’(Co III ) were obtained in excellent yields, and their characterisation by 1 H NMR, IR, mass spectroscopy, elemental analysis and X-ray diffraction revealed that they were of diamagnetic nature, octahedral geometry with the cobalt centre and meridional configuration. The redox behaviour of these complexes shows an irreversible reduction wave with a peak potential in the range -1.9 to -1.2 V. Upon reduction, the complexes decompose, giving rise to a redox pattern compatible with the formation of bis[2-[(octylimino)methyl]-1-pyrenolato-N,O] cobalt(II). Keywords: Coordination chemistry, Cobalt, Pyrene, π-Expanded ligand, Salicylaldimine. References : [1] Luong Xuan Dien, Ken-ichi Yamashita, Motoko S. Asano, Ken-ichi Sugiura, Synthesis of a pyrene-based π-expanded ligand and the corresponding platinum(II) complex, Bis[2-[(octylimino)methyl]-1-pyrenolato-N,O] platinum(II), Inorganica Chimica Acta 432 (2015) 103-108. https://doi.org/10.1016/j.ica. 2015.03.038. [2] Luong Xuan Dien, Ken-ichi Yamashita, Ken-ichi Sugiura, Metal Complexes of π-Expanded Ligands (2): Synthesis and characterizations of bis[2-[(octylimino)methyl]-1-pyrenolato-N,O] palladium(II) and the stabilized vacant dx2-y2 orbital, Polyhedron 102 (2015) 69-74. https://doi.org/10.1016/j.poly.2015.07.043. [3] Luong Xuan Dien, Nguyen Xuan Truong, Ngo Duc Quan, Ken-ichi Yamashita, Ken-ichi Sugiura, Syntheses and structures of Ni(II) complexes containing 2 alkyliminomethyl pyrene ligands, VNU Journal of Science 34 (4) (2018) 16-20. https://doi.org/10.25073/2588-1140/vnunst.4809. [4] Robert D. Jones, David A. Summerville, Fred. Basolo, Synthetic oxygen carriers related to biological systems, Chem. Rev. 79 (1979) 139-179. https://doi.org/10.1021/cr60318a002. [5] Kuninobu Kasuga, Takeo Nagahara, Akira Tsuge, Kunihisa Sogabe, Yasuo Yamamoto, The preparation and some properties of cobalt(II) schiff base complexes and their molecular oxygen adducts, Bull. Chem. Soc. Jpn. 56 (1983) 95-98. https://doi.org/10.1246/bcsj.56.95. [6] H. Pellissier, H. Clavier, Enantioselective cobalt-catalyzed transformations, Chem. Rev. 114 (2014) 2775-2823. https://doi.org/10.1021/ cr4004055. [7] R. H. Crabtree, Energy Production and Storage: Inorganic Chemical Strategies for a Warming World, first ed., John Wiley & Sons, West Sussex, 2010. [8] P. Sravanthi, C. Chandrakala, KS. Nagaraja, B. Jeyaraj, Development of cobalt Schiff base precursors for nanocrystalline cobalt oxide thin film by thermal CVD method, International journal of pharmaceutical, chemical and biological sciences 5 (1) (2015) 112-125. http:/ /www.ijpcbs.com/files/volume5-1-2015/12.pdf. [9] B. O. West, Complexes of tervalent cobalt with N-substituted salicylideneimines, J. Chem. Soc. 0 (1960) 4944-4947. https://doi.org/10. 1039/JR9600004944. [10] A. Ourari, Y. Ouennoughi, S. Bouacida, Tris(2-{[2-(4-meth¬oxy¬phen¬yl)eth¬yl]imino-meth¬yl}phenolato-κ2N,O1)cobalt(III), Acta Cryst., E68 (2012) m803-m804. https://doi.org/10.1107/ S1600536812023033. [11] A. Chakravorty , R.H. Holm, Identification of the geometrical isomers of some tris-chelate cobalt(III) complexes by nuclear resonance, Inorg. Chem. 3 (1964) 1521-1524. https://doi. org/10.1021/ic50021a010. [12] S. Li, S.-B. Wang, K. Tang, Y.-F. Ma, Tris [2-(propyliminomethyl)phenolato-κ2 N,O]cobalt(III), Acta Cryst. E64 (2008) m823. https://doi.org/ 10.1107/S1600536808014074.